Safety, tolerability, and pharmacokinetics of repeated oral doses of 2-hydroxybenzylamine acetate in healthy volunteers: a double-blind, randomized, placebo-controlled clinical trial - Lisa M. Pitchford; Patricia M. Driver; John C. Fuller; Wendell S. Akers; Naji N. Abumrad; Venkataraman Amarnath; Ginger L. Milne; Sheau-Chiann Chen; Fei Ye; L. Jackson Roberts; M. Benjamin Shoemaker; John A. Oates; et al. (BMC, 2020)
Abstract Background 2-Hydroxybenzylamine (2-HOBA) is a selective dicarbonyl electrophile scavenger being developed as a nutritional supplement to help protect against the development of conditions associated with dicarbonyl electrophile formation, such as the cognitive decline observed with Mild Cognitive Impairment or Alzheimer's disease. Methods This study evaluated the safety, tolerability, and pharmacokinetics of repeated oral doses of 2-HOBA acetate (500 or 750 mg) administered to healthy volunteers every eight hours for two weeks. The effects of 2-HOBA on cyclooxygenase function and cerebrospinal fluid penetrance of 2-HOBA were also investigated. Results Repeated oral administration of 2-HOBA was found to be safe and well-tolerated up to 750 mg TID for 15 days. 2-HOBA was absorbed within 2 h of administration, had a half-life of 2.10-3.27 h, and an accumulation ratio of 1.38-1.52. 2-HOBA did not interfere with cyclooxygenase function and was found to be present in cerebrospinal fluid 90 min after dosing. Conclusions Repeated oral administration of 2-HOBA was found to be safe and well-tolerated. These results support continued development of 2-HOBA as a nutritional supplement. Trial registration Studies are registered at ClinicalTrials.gov (NCT03555682 Registered 13 June 2018, NCT03554096 Registered 12 June 18).